Private companies' engagement in the labour market integration of refugees: An exploratory study of the city of Stuttgart, Germany - Masooma Torfa; Christine Bosch; Regina Birner; Hannes Schammann (International Migration, 2022)
Private companies of all sizes may engage in the integration of refugees into the labour market. Taking the case study of the highly industrialised German city of Stuttgart, this study explores the motivation of (a) private large-scale international enterprises including (automotive and high-tech companies) and (b) family-owned small- to medium-sized companies (private social enterprises, suppliers to the automotive industries, architecture, and engineering companies) to do so. The research further explores the companies' challenges, opportunities and the lessons learned throughout the process. Utilising the principles of Grounded Theory, a qualitative case study approach is applied with in-depth interviews with private companies, civil society, public private partnerships and experts. The findings show that the arrival of a large number of refugees during 2015/2016 has increased the engagement of the companies, increased their cooperation with other sectors, and has correspondingly led to some innovative initiatives in refugees' labour market integration and policy advocacy. The call for the engagement of the private sector and the existence of employment-related policies such as tolerated work permits (Ausbildungsduldung/Beschäftigungsduldung) were essential to create sufficient incentives for private companies to engage in the training and employment of refugees. However, the insecure residence permits and bureaucratic procedures in the public sector mostly discouraged their engagement. Our research shows that the two company types had different possibilities, different approaches towards refugees and faced different challenges while engaging in refugee labour market integration.
Keywords: 300